The influence of household environment on caregivers' overload of children with cerebral paralysis - 10.4025/actascihealthsci.v34ispec.10264 - Alessandra Alcides de Sá Santos; Jamille Alves Araújo; Marlizete Maldonado Vargas; Cristiane Costa da Cunha Oliveira (Universidade Estadual de Maringá, 2012)
The environment is considered an extremely important factor in individuals' health promotion and life quality. The influence that the environment exerts on caregivers' lives is due to all the complications they have to experience. Current study investigates the influence of family environment on the overload of caregivers of children with cerebral paralysis. The research comprised 21 caregivers, whose overload intensity was assessed by three instruments: a caretaker characterization form, Zarit Caregiver Burden Interview (ZBI) and an environmental characterization protocol. Results showed that all caregivers revealed a certain level of overload (52.4% intense and 47.6% moderate). Physical modifications were observed in 52.4% of the residences under survey but none was undertaken by a professional in rehabilitation. A statistically significant correlation occurred in children's spatial movement (p=0.031). Research suggests that caregivers of children with cerebral paralysis are overburdened due to the health care activities and that the environment constitutes a risk factor.